Clinicopathological Characteristics of Colorectal Cancer in the Anatomical Pathology Laboratory of Dr. M. Djamil Padang 2017-2020 - Muhammad Farhan Hasan; Noza Hilbertina; Deddy Saputra (International Journal of Health and Social Behavior, 2024)
Colorectal cancer is a malignant epithelial tumor originating from colorectal mucosa. Clinicopathology factors including age, gender, location, histopathological type, differentiation, depth of invasion, lymph node metastasis, and lymphovascular invasion are known affect the prognosis. This study aims to determine the clinicopathological characteristics of colorectal cancer at Anatomical Pathology Laboratory RSUP. Dr. M. Djamil Padang in 2017-2020 This study was descriptive observational with total sampling technique from medical records. Samples included all colorectal cancer patients in 2017-2020 who were fulfilled inclusion criteria, with total 251 samples. The results showed that the most patiens were female (52.2%), the age group were > 50 years (66.1%), mostly located in the rectosigmoid (71.7%). Most of the histopathological types were adenocarcinoma (79.7%), with low grade differentiation (88.8%). More than a half of tumor invasion was at T3 (58.2%). Mainly metastatic status to lymph nodes was Nx (54.2%) and lymphovascular invasion were positive in 60% samples that included the lymphovascular invasion examination. The conclusion of this study is most of colorectal cancer in Anatomical Pathology Laboratory RSUP. Dr. M. Djamil Padang in 2017-2020 are in advanced stage, Early detection needs to be done so that colorectal cancer can be diagnosed at an early stage.